Identifying Parenting Practices: An Initial Step in Setting Up Parenting Program in School (Malaysian Management Journal, 2004)
The purpose of this study was to identify the levels of parenting practices among Malay and Chinese parents as perceived by their children. A total of 217 students responded to a questionnaire with items pertaining to their mothers’ and fathers’ demandingness and responsiveness practices. Findings revealed most of the Malay and Chinese parents in this study were perceived by their children to be low in demandingness and responsiveness. The only difference reported was between mothers’ and fathers’ demandingness. The response to each item in the demandingness and responsiveness measurement would be a guide to what should be included in the parenting course program. Implications for further research were also discussed.